Keep healthy for little kids going to big school - Bates, Eleanor; Beets, Sally; Mewati, Gunjan; Nayak, Bhagyashree; Rais, Roohi; Stevenson, Emily (London Dorling kindersley Limited, 2021)
Learn all the super-important skills you need to stay healthy in this book about early life skills. No matter what grown-ups tell you, being little is hard work; there's so much to learn when it comes to staying healthy - from how to wash your hands properly, to learning how to keep calm, to remembering what foods are good for you - and a whole bunch of other things too
Scientific notions
Keywords: Science